One in Seven and a Half: Local Activism against the Global Climate Crisis - Saveski, Zdravko (Identities: Journal for Politics, Gender and Culture, 2019)
The climate crisis has become not only serious but urgent problem too. A lot of years have been wasted in palliative measures that have not solved the problems. And those wasted years have closed the space to search for solutions inside the framework of some kind of Green capitalism. At the present time, solutions to the climate crisis are still possible, but they will require drastic, even systematic measures. This article analyzes the role of capitalism in creating and deepening climate crisis. Capitalism is not only a type of economy but a type of society. It has achieved hegemony in the field of ideas and values, socializing people and internalizing its values among the losers of the system, as well as among its beneficiaries. Due to this, overcoming capitalism is not an easy or simple task. However, as it is argued in the article, the only humane alternative to overcome climate crisis is to overcome capitalism as a type of economy and a type of society. Author(s): Zdravko Saveski Title (English): One in Seven and a Half: Local Activism against the Global Climate Crisis Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019) Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 8-17 Page Count: 10 Citation (English): Zdravko Saveski, “One in Seven and a Half: Local Activism against the Global Climate Crisis,” Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019): 8-17.